Muslim Family Strategic Management: Analysing the Balance Between Academic Achievement and Moral Values in the Digital Age - Reni Supriani; Jasiah Jasiah; Ajahari Ajahari (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study aims to analyze in depth the implementation of strategic management in character education within Muslim families in Pangkalan Bun, Central Kalimantan. Using a qualitative case study research design, this study involved 13 parents of students at SIT (SDIT & SMPIT) as purposively selected key informants. Primary data were collected through structured interview techniques that explored parental vision, time organization, and supervisory functions at home. The data were then systematically analyzed using thematic analysis techniques. The findings reveal that although parents place adab (Islamic manners and ethics) as the highest emotional and spiritual priority, in daily managerial practices their attention remains dominated by academic orientations that are technical and quantitative in nature. Furthermore, digital technology or gadgets were identified as the main disruptive variable as well as a competitor to parental authority, capable of distorting children’s moral values through the “hidden curriculum” embedded in social media. This study recommends the need for recalibrating family management functions by adopting the POAC framework (Planning, Organizing, Actuating, Controlling), which positions adab as the primary foundation and core value prior to intellectual achievement